Analysis and Development of Temperature Sensor in Polymer Processing - W., Chaiwattanpipat; M., Panapoy; A., Tangsongcharoen; N., Sombatsompop (Engineering and Applied Science Research, 2013)
<span style="line-height: 115%; font-family: "AngsanaUPC","serif"; font-size: 16pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH;">This work was part of ongoing investigations into study and development of temperature sensing devices for measuring temperature of flowing polymer melts in polymer processing equipment. The proposed temperature sensor uses the principle of thermocouple in which its design is similar to that originally proposed by wood, Sombatsompop and their co-workers. The main objective of this article was to investigate in more details as to the characteristics of materials used for making the sensor, including the properties, costs, avaibility, and robustness of the sensor. The reliability and efficiency of the proposed sensor were also examined. It was found that the sensor was reliable, simple in design and manufacture, low in cost, easy to calibrate and use. In addition, the sensor could be utilized to measure multi-point temperatures simultaneously at elevated temperatures (up to 300 oC) without any obvious damages. With the use of this sensor, the effects of heat conduction and shear heating on the measured temperature were minimized.